2021
DOI: 10.1111/exd.14346
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐assisted epicutaneous immunization to target human skin dendritic cells

Abstract: Classical vaccines are commonly administered by subcutaneous or intramuscular injection. This is mainly for practical reasons such as the ease of manipulation. Intradermal injection ("Mantoux technique") is known to have several advantages 1 but is hampered by the required skills of injection-delivering personnel, especially when dealing with mass vaccinations. 2,3 Therefore, a wide variety of approaches (e.g. microneedles, 4,5 topical patches, 6 high pressure "guns" 7 ) are being tested to facilitate intrader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The human skin explant model is a suitable tool to study antigen delivery to skin DC in their natural environment, which is of immense interest for translating knowledge into the clinics [ 27 , 34 , 35 ]. This model allows to investigate human skin DC function in a vaccination setting as close as possible to the in vivo situation.…”
Section: Resultsmentioning
confidence: 99%
“…The human skin explant model is a suitable tool to study antigen delivery to skin DC in their natural environment, which is of immense interest for translating knowledge into the clinics [ 27 , 34 , 35 ]. This model allows to investigate human skin DC function in a vaccination setting as close as possible to the in vivo situation.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that local attenuation of RTN1A functionality with an N-terminus-targeting ab caused significant changes in the morphology of rLCs, leading to a roundish cell body with reduced dendrite length and dendrite distribution. Labelling of rLCs in human skin ex vivo 58 and in mouse skin in vivo 59 has been successfully employed before, yet in this study we targeted an intracellular protein. These observations led us to conclude that RTN1A is promoting elongation of dendrites in rLCs.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that local attenuation of RTN1A functionality with an N-terminus-targeting ab caused significant changes in the morphology of rLCs, leading to a roundish cell body with reduced dendrite length and dendrite distribution. Labeling of rLCs in human skin ex vivo ( Tripp et al, 2021 ) and in mouse skin in vivo ( Flacher et al, 2010 ) has been successfully employed before, yet in this study we targeted an intracellular protein. These observations led us to conclude that RTN1A is promoting elongation of dendrites in rLCs.…”
Section: Discussionmentioning
confidence: 99%